(untitled) (Journal of Economic Research & Business Administration, 2015)
Abstract. In the domestic insurance market it is impossible to recognise a state of affairs satisfactory. Dynamics of the basic indicators of the insurance market against fast growth of a national economy is represented obviously insuffi cient. The insurance market of Kazakhstan still lags behind in development other sectors of the fi nancial market, the majority from which develops the rates considerably advancing growth of economy. Insuffi cient development of the market of insurance services is caused by a number of unresolved problems of objective and subjective character, on what, according to the authorised body, more considerable period of time is required. The facts set forth above are the main problems on a way of perfection of the insurance market of our country at economic level. In this regard, in work are offered a way of their elimination and primary factors of infl uence on developments of the insurance market.